The Effect of Compensation and Rewards on Employee Performance: A Case Study of PT Trimega Pasivic Indonesia - Muh Nur (JMET: Journal of Management Entrepreneurship and Tourism, 2026)
This study aims to examine the effect of compensation and rewards on employee performance at PT Trimega Pasivic Indonesia. The research employs a quantitative approach using multiple linear regression analysis, with data collected through questionnaires distributed to employees directly involved in the company’s operational activities. The independent variables in this study consist of compensation and rewards, while the dependent variable is employee performance. The results of the analysis indicate that both compensation and rewards have a positive and statistically significant effect on employee performance, both simultaneously and partially. These findings underscore the critical importance of implementing a fair and well-structured compensation and reward system to enhance employee productivity and job satisfaction, which ultimately contributes to the overall success of the company. This study is expected to provide theoretical contributions to the development of human resource management literature, as well as practical implications for organizations in optimizing employee performance management.